A study identifying factors influencing decision making in dynamic emergencies like urban fire and rescue settings. Issue 2 (7th October 2014) - Launder, David; Perry, Chad
Abstract : Purpose: – There has been little research about incident management decision making within real-life, dynamic emergencies such as urban fire settings. So this research addresses the research problem: how do incident managers make decisions in urban fire settings? These decision behaviours cover five areas: assessment of the fireground situation, selection of a decision strategy, determination of incident objectives, deployment and management of firefighting resources and ongoing review of the incident. The paper aims to discuss these issues. Design/methodology/approach: – Case research was used to examine management of different types of fires, through in-depth interviews with a range of incident managers. Findings: – This research identified five key behavioural elements associated with incident management in urban fire settings such as their application of a mix of recognition-primed, value based, procedural and formal decision strategies throughout the course of an incident rather than a single style. Research limitations/implications: – The in-depth framework of decision making could provide foundations for later research about other emergency settings. And this research is limited to analytic generalisation (Yin, 2009); so quantitative research such as surveys and large scale interviews could be done to further extend the research for statistical generalisation. Practical implications: – The decision procedures uncovered in this research will assist incident managers in many emergencies, assist policy making and foster the development of future incident managers. Originality/value: – The findings expand the knowledge of how incident managers develop situation awareness, make decisions and plans, implement them, and review the incident as it evolves. Another contribution is the comprehensive framework of decision making developed from these findings.